Analysis of Glucosinolate Content, Composition and Expression Level of Biosynthesis Pathway Genes in Different Chinese Kale Varieties - Lu Tong; Shanhan Cheng; Honghao Lv; Chengzhi Zhao; Jie Zhu; Pingwu Liu; Zhiwei Wang; Limei Yang; Yangyong Zhang (Horticulturae, 2021)
The content and component of glucosinolates in edible stems and leaves of eight Chinese kale varieties from Japan and eight varieties from China were determined by HPLC-MS. Simultaneously, the expression levels of glucosinolate biosynthesis pathway genes from four varieties with high and low total glucosinolate contents were analyzed by the qRT-PCR method. Four types of aliphatic glucosinolates (A-GLSs: GRA, SIN, GNA and GER) and indole glucosinolates (I-GLSs: 4-HGBS, GBS, 4-MGBS and NGBS) were detected in the stems and leaves of 16 varieties, and no aromatic glucosinolates (R-GLSs) were detected. A-GLSs account for more than 80.69% of the total content of total glucosinolates (T-GLSs), in which GNA and GRA are the main components of stems and leaves. Among Japanese varieties, QB1 has higher content of A- and T-GLSs, while that of XLB was lower; however, the corresponding varieties were ZH and DSHH in Chinese varieties. Among the above four varieties, the expression levels of SOT16, CYP83B1, SOT17, CYP83A1 and MAM1 genes were significantly higher in the varieties with higher GLSs; the expression levels of SOT16 and CYP83B1 were consistent with the content of I-GLSs; and SOT17, CYP83A1 and MAM1 expression levels were consistent with A-GLSs content. At the same time, the expression levels of SOT16 and CYP83B1 in the leaves were higher than those in the stems. CYP83A1 and MAM1 genes were less expressed in the leaves than in the stems of lower content varieties. It is speculated that these genes may be the key genes regulating GLS biosynthesis in Chinese kale.